KEAWETAN ALAMI KAYU MERANTI MERAH (Shorea leprosula Miq.) HUTAN ALAM DAN HUTAN TANAMAN DARI SERANGAN JAMUR PELAPUK KAYU - riah, Khae; Indrayani, Yuliati; Husni, Harnani (JURNAL HUTAN LESTARI, 2014)
This research was carried out by using JIS method to evaluate natural durability of red meranti (Shorea leprosula Miq.) plantations using Silin system. For comparison, the similiar method was done on S. leprosula from natural forests. This study used a factorial CRD (completely randomized design) with treatment of Raw Materials (S. leprosula from Natural Forest and from Plantation Forest) and Stem Position (Bottom, Middle, and Upper). Each treatment were tested against wood rot fungi such as Tyromyces palustris (brown rot) and Pycnoporus sanguineus (white rot) to determine the percentage of weight loss. The results show that T. palustris give significant effect on reducing the weight loss the wood of S. leprosula, while the interaction between the two factors was not significant. Similiar result was note on P. sanguineus that the factors of raw materials and the position of the rod give significant effect on weight loss of S. leprosula. While the interaction of these two factors significantly affect S. leprosula weight loss. The results showed that, S. leprosula timber from natural forests and plantations are tested against both types of wood rot fungi has met the standard of weight loss is required by JIS that is < 30% for brown rot fungi and < 15% for white rot fungi. It is conclude that the S. leprosula wood from plantations forest supply can be used to replace wood from natural forest S. leprosula to fulfill the require of wood. Key word : Shorea leprosula wood, Natural durability, Tyromyces palustris, Pycnoporus sanguineus, weight loss